(3bhI GdeN GdPgfjIs (3GdbOQGJ GdPgfjI hGSGdjH JbhjI GdPGcQIs - (3HQGjf, L(B. (3Hs; (3MSf, eMeOs ((3GdbGgQIs (3OGQ fHJI ddfTQs, 2019)
(3GdYbhd bhI cHjQI dG JUOb gd acQJ Cf JJCed jheG Ybdc hJQi cja jYed ? Efc SJba ePghdG MjGd GdbhI GdOGNdjI dYbdc heY Cfc JYde Cf Ybdc jeJdc bhI cHjQI heY gPG CfJ dG JSJNOe CcKQ ef (B10 % (3abW ef Ybde Ydjc Cf JYed dcj JSJKeQ bhIJ Ybdc GdHGbjI hdG JJQcgG egedI Ohf GSJKeGQ(B. (3dbO GcJa GdYdeGA YdeG LOjOG jSei GdeQhfI GdYUHjI jecf Ief NdGdg JZjjQ fXGe Ybdc HSghdI, Yde JZjjQ GdJacjQ Ch GdJMce aj GdOeGZ jSGYOc aj eYQaI fbGW VYac hJMhjdgG Edi fbGW bhIs
(3eJhGaQ efg GdWHYI GdGhdi dYGe (B2019 (3HecJHI eUQ aQY GdRGhjI GdMeQGAs
(3eJhGaQ efg GdWHYI GdKGfjI dYGe (B2019 (3HecJHg eUQ GdYGeg(B-(3aQY GdhGOi GdLOjOs
1 2 7 13
Keywords: (3GdJPcQs; (3GdPGcQIs; (3GdYbds